Development of English Learning Model Based on Local Wisdom with Blended Learning Approach Using Macromedia Flash at SMPN Satu Atap Tunda Island - Dede Rohadi Fajri; Sisca Wulansari Saputri (Universitas Pendidikan Mandalika, 2021)
The aim of the research is to create a learning media model for English that uses the Macromedia Flash program, as well as to assess the viability of utilizing Macromedia Flash-based learning media to assist English. This study is a Research and Development (R & D) project with several stages. (1) Analysis stages, such as identifying Learning Media objectives and student characteristics; (2) Design stages, such as designing learning materials and learning media design using the Macromedia Flash program; (3) Production stages, such as producing learning materials, authoring materials, and editing learning materials; (4) Stages of evaluation, including Material Expert Review, Media Expert Review, and Student Testing. The findings demonstrate that the English learning media products adhere to research and development guidelines and are successful in the learning process for SMPN Satu Atap Pulai Tunda students.